Penerapan Metode Simple Additive Weighting (SAW) Dalam Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik CV. Lestari Indojaya - Sonhaji; Sri Hartati; Sri Lestari (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
One of the important factors in quality human resources in a company to be able to run the business process properly in accordance with the vision and mission that has been set by the company. CV. Lestari Indojaya is one of the companies engaged in procurement and education which was founded in 2000. In order to encourage the creation of increasing performance productivity, CV. Lestari Indojaya carries out the selection of the best employees. Decision support systems can help decision makers to get recommendations for the best employees using the SAW (Simple Additive Weighting) method. In this study, the data used came from internal data and external data. There are several criteria needed to help decision makers choose the best employees, namely discipline, quality of work, cooperation and behavior. Based on all the criteria and alternatives in this study, Darwansyah was the best employee at CV. Lestari Indojaya with a total preference value of 2.875. The SAW method is an effective and practical method in calculating the best employee recommendations at CV. Lestari Indojaya so that decision makers can consider these recommendations according to the specified priorities.